Reperfusion after ischemic stroke is associated with reduced brain edema. Issue 10 (October 2018) - Irvine, Hannah J; Ostwaldt, Ann-Christin; Bevers, Matthew B; Dixon, Simone; Battey, Thomas WK; Campbell, Bruce CV; Davis, Stephen M; Donnan, Geoffrey A; Sheth, Kevin N; Jahan, Reza; Saver, Jeffrey L; Kidwell, Chelsea S; et al.
Rapid revascularization is highly effective for acute stroke, but animal studies suggest that reperfusion edema may attenuate its beneficial effects. We investigated the relationship between reperfusion and edema in patients from the Echoplanar Imaging Thrombolysis Evaluation Trial (EPITHET) and Mechanical Retrieval and Recanalization of Stroke Clots Using Embolectomy (MR RESCUE) cohorts. Reperfusion percentage was measured as the difference in perfusion-weighted imaging lesion volume between baseline and follow-up (day 3–5 for EPITHET; day 6–8 for MR RESCUE). Midline shift (MLS) and swelling volume were quantified on follow-up MRI. We found that reperfusion was associated with less MLS (EPITHET: Spearman ρ = −0.46; P  < 0.001, and MR RESCUE: Spearman ρ = −0.49; P  < 0.001) and lower swelling volume (EPITHET: Spearman ρ = −0.56; P  < 0.001, and MR RESCUE: Spearman ρ = −0.27; P  = 0.026). Multivariable analyses performed in EPITHET and MR RESCUE demonstrated that reperfusion independently predicted both less MLS (ß coefficient = −0.056; P  = 0.025, and ß coefficient = −0.38; P  = 0.028, respectively) and lower swelling volumes (ß coefficient = −4.7; P  = 0.007, and ß coefficient = −10.7; P =  0.009, respectively), after adjusting for age, sex, NIHSS, admission glucose and follow-up lesion size. Taken together, our data suggest that even modest improvement in perfusion is associated with less brain edema in EPITHET and MR RESCUE.